Thomas “Mukanya” Mapfumo and Songs of Protest in Colonial and Post-Independence Zimbabwe - Muranda, Richard; Chimbudzi, Weston; Maguraushe, Wonder (Oxford University Press, 2022)
This bibliography covers scholarship on selected protest songs of the musician Thomas “Mukanya” Mapfumo (b. 1945) that were written in colonial and postcolonial Zimbabwe. In keeping with the Marxist cultural theoretical orientation that is evident in research on this subject, the organization of these entries traces the sociopolitical engagement of Mapfumo’s songs that reflect praise and dissent during the Second and Third Chimurenga wars of political liberation, respectively. Discourse on Zimbabwe’s economic challenges has positive and negative interpretations. Mamdani 2005 and Bond and Manyanya 2002 (both cited under General Overview) state that the Zimbabwe African National Union-Patriotic Front (ZANU-PF) inherited an economy that had already suffered due to pre-independence policies. Dossa 2007 (under General Overview) argues that development is meant to perpetuate Western dominance. Manjengwa 2007 (under General Overview) blames the ruling party’s top-down approach in implementing development programs. The first section of the bibliography analyzes the songs “Pfumvu paruzevha,” “Kuyaura,” “Chiruzevha chapera,” and “Tumira vana kuhondo,” which Mukanya composed to express the experiences of Zimbabweans during colonialism. Zimbabweans’ way of life was disrupted and Mukanya mirrored this cultural upset through protest songs. The songs resonated well with the ideology of the ZANU-PF. Soon after independence, Mapfumo sang celebration songs (“Zimbabwe” and “Rakarira jongwe”). The second section examines protest songs penned after independence (“Varombo kuvarombo,” “Ndiani waparadza musha,” “Musatambe nenyika,” “Disaster,” “Corruption,” “Mamvemve,” “Maiti kurima hamubvire,” “Chauya chauya,” and “Ndangariro”). The scenario deteriorated due to alleged misgovernance by the ruling ZANU-PF elite, a situation that attracted Mukanya’s criticism. The bibliography traces how the transition of ZANU-PF from heroes to villains is portrayed through Mukanya’s music. During the armed struggle, Mapfumo sided with the liberation war movement. This changed after independence, and Mapfumo allegorically poses questions pointing at the empty promises ZANU-PF leaders made to uplift Zimbabweans’ standard of living. Mukanya sang about the contested land redistribution in Zimbabwe. Consequently, Mapfumo was stalked by state repressive agents until he fled to live in exile in the United States in 2000. He yearned for Ubuntu philosophy, nationalism, and unity. People may differ ideologically, but they ought to accept one another as a nation. This fosters positive peace, which Zimbabweans have yearned for over four decades. Mapfumo wants people to be economically empowered. He has been incarcerated before and he is fearless. Chimurenga music is a voice for the downtrodden masses. Mukanya’s songs that have explicit political messages were banned from airplay by the government. Mapfumo has remained united with the people he is fighting for despite living in exile. Mapfumo uses music to complain about the people’s suffering. He bears memories about Zimbabwe that remain engrained in Chimurenga music in the backdrop of ZANU-PF hegemony. He has called for free and fair elections because Zimbabweans have a right to choose leaders, but election results have been contested since 2000.